PEMANFAATAN BETON NON-PASIR SEBAGAI ALTERNATIF PERMEABLE PAVING BLOCK DENGAN MENGGUNAKAN AGREGAT KASAR LOKAL SUMENEP BERUPA KERIKIL BATU PECAH - Deshariyanto, Dwi; Fansuri, Subaidillah; Diana, Anita Intan Nura (Fakultas Teknik, Universitas Wiraraja, 2025)
Non-sand concrete or porous concrete is made by reducing the use of fine aggregates (sand). The high porosity of this concrete acts as a water absorption capacity that allows the concrete to absorb rainwater and water from other sources above it. Based on the existing problems, this study examines the compressive strength, water absorption capacity, ideal proportions, and application of paving blocks made from sandless concrete using local coarse aggregates. The objective of this research is to determine the compressive strength, water absorption capacity, ideal proportions, and application of paving blocks. This study uses a ratio of 1Pc:6 Ak, 1Pc:8 Ak, and 1Pc:10 Ak with a phase of 0.4, and this research method uses in-depth analysis techniques. The 1Pc:6Ak ratio has the highest average compressive strength of 6.3 Mpa. The 1Pc:6Ak ratio had an average water absorption of 26 ml/second. The ideal proportion of the three ratios studied is 1Pc : 6Ak with a compressive strength of 6.3 MPa and a water absorption capacity of 26 ml/second. A compressive strength of 6.3 MPa is classified as grade D with a water absorption capacity of 26–31.75 ml/second.